Nephrotoxic Effects of Folic Acid on Wistar Rats - Evi Lusiana; Theodorus; Nia Savitri Tamzil; Nita Parisa; Riana Sari Puspita Rasyid; Bintang Fajarullah; Bella Puspita Aziatri (Majalah Kedokteran Sriwijaya, 2023)
Nephrotoxic effect of folic acid in wistar rats. There is an inadequate amount of scientific research on the effects of high-dose folic acid induction on the kidneys of Wistar rats, as well as research on the development of experimental animal models of Acute Renal Failure (ARF). The objective of the study was to determine the nephrotoxic effects that induce ARF in Wistar rats by administering high doses of folic acid. In September and October 2022, in vivo, experimental research was conducted at the Animal House of the Faculty of Medicine, Sriwijaya University, and the Palembang Health Laboratory Center. Contains 4 treatment groups: placebo (NaCl 0.9%), KIAF I at 100 mg / kgBB, KIAF II at 125 mg / kgBB, and KIAF III at 250 mg / kgBB single dose intraperitoneally; 8 wistar rats per group. Data analysis utilizing the SPSS Statistic 26 Paired T test, Independent T test, and PostHoc Test. The data for rat body weight (p=0.099) are homogenous. The concentrations of creatinine (p=0.119) and urea were homogeneous and normally distributed (p>0.05). KIAF I (p=0.010), KIAF II (p=0.000), and KIAF III (p=0.005) effectively increased the mean creatinine levels between days 0 and 14 (p=0.010). The difference between KIAF II and placebo was statistically significant (p=0.032). There was no optimal dose group (p>0.05) for increasing creatinine levels. KIAF II was efficacious at increasing the mean urea level on days 0 and 14 (p = 0.036). The difference between KIAF II and placebo was statistically significant (p=0.005). The optimal concentration of KIAF II (p=0.002) was found to increase ureum levels. KIAF II (p=0.002) is the optimal dose for increasing ureum levels in Wistar rats, but not creatinine levels, which causes ARF.